Peningkatan Kemampuan Mengenal Huruf Melalui Metode Bermain Kartu Interaktif Pada Anak Usia 5-6 Tahun di TK Punai - Khusnul Khotimah; Shanda Agusti Ramadani; Windri Bella Hovina; Akmillah Ilhami (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
This study aims to improve letter recognition skills in children aged 5–6 years at TK Punai, Tanjung Seteko Village, Indralaya Subdistrict, through the implementation of interactive card play methods. The research employs a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of this study were 16 children in group B, aged 5–6 years. Data collection techniques included observation and documentation, while data analysis utilized both qualitative and quantitative approaches. The results showed an improvement in children’s letter recognition ability, with 81% in the first cycle and an increase to 95% in the second cycle. Thus, the interactive card play method proved effective in enhancing children's letter recognition skills. This study also had a positive impact on children's cognitive development, concentration, and memory. Interactive card games can stimulate children to think actively, develop their ability to remember letter shapes and names, and train eye-hand coordination.